Preventive therapy of antioxidant vitamins against the blood choline levels in cardiovascular patients - Ali, Muhammad Asif; Nasir, Muhammad; Pasha, Talat Naseer; Javid, Imran; Muzaffar, Rizwana; Rashid, Anjum; ur Rehman, Habib; Gondal, Tanweer Aslam; Imran, Muhammad; Sharifi-Rad, Javad; Iqbal, Zafar; Ahmed, Sheraz (Cellular and Molecular Biology, 2020)
Therapeutic role of antioxidant against lipid profile and lipoprotein (choline) was observed by the different researchers, but clinical evidences required about the use of antioxidant vitamins against the lipoproteins. Patients with clinical evidence of cardiovascular disease (CVD) confirmed by standard diagnostic techniques were followed. Newly or recently, diagnosed case subjects were recruited wherever possible. At least 120 cases, subjects both male and female with CVD were selected from a local hospital. Four groups developed on the base of antioxidant therapy and blood samples were collected at zero day, 20 days, 40 days and 60 days. vitamins C and E are the major dietary cellular and lipid antioxidants, respectively; we found no evidence to support the use of vitamin or antioxidant supplements in the reduction of mortality. However, they are helpful in the management of prevention of cardiovascular disease.